2015
DOI: 10.1021/ar5002999
|View full text |Cite
|
Sign up to set email alerts
|

Markov State Models Provide Insights into Dynamic Modulation of Protein Function

Abstract: ConspectusProtein function is inextricably linked to protein dynamics. As we move from a static structural picture to a dynamic ensemble view of protein structure and function, novel computational paradigms are required for observing and understanding conformational dynamics of proteins and its functional implications. In principle, molecular dynamics simulations can provide the time evolution of atomistic models of proteins, but the long time scales associated with functional dynamics make it difficult to obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
293
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 257 publications
(293 citation statements)
references
References 58 publications
(131 reference statements)
0
293
0
Order By: Relevance
“…However, both the equilibrium and Sharpe-Schoolfield models may represent over-simplifications of the highly dynamic structures of proteins (Shukla et al, 2015). Rather than occurring in a small number of conformations (e.g.…”
Section: Effects Of Temperature At the Level Of Single Proteinsmentioning
confidence: 99%
“…However, both the equilibrium and Sharpe-Schoolfield models may represent over-simplifications of the highly dynamic structures of proteins (Shukla et al, 2015). Rather than occurring in a small number of conformations (e.g.…”
Section: Effects Of Temperature At the Level Of Single Proteinsmentioning
confidence: 99%
“…[12][13][14]16,[19][20][21][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Building a MSM involves decomposing the phase space sampled by one or more MD trajectories into a set of discrete states and estimating the (conditional) transition probabilities between each pair of states. However, there are many ways to perform the state decomposition, and the choice of MSM building protocol can introduce subjectivity into the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Any kinetic information has been gleaned from experimental techniques such as SPR which provide the rates of association and dissociation. However, details of these processes have only been available from a few Brownian dynamics simulations and more recently long timescale atomistic simulations coupled to markov chain analyses 32,33 . In a recent Brownian dynamics study, based on kinetic arguments, we showed that residues on the MDM2 surface outside the p53 binding pocket could stabilize the p53-MDM2 encounter complex, a state that is formed prior to the formation of the final bound complex, by increasing p53 residence times and allowing for allosteric interactions with MDM2 34 .…”
Section: Introductionmentioning
confidence: 99%